A survey on the microbiological quality of mixed feeds and feedstuffs l'sed in hatay province - Zeynep Erdoğan; Özkan Aslantaş (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine Ihe microbiological quality of 50 mixed feeds and feedstuffs samples by examining the total counts of bactena and fungi obtained from Hatay, Antakya. It was also studied that the isolation and identification of Salmonella spp. and other bacteria ahd lungi spp. in the same samples. Isolated microorganisms were found to be as 46 % Bacillus spp., 36 % Pseudomonas spp.. (34 % Staphylococcus spp., 32 % Enterobacter spp., 30 % Micrococcus spp., 24% Streptococcus spp., 14 % Actinobacillus spp., 14 % Klebsiella spp., 12 % E.coli, 8 % Proteus spp., 2 % Penicillium spp. in the analysed feed samples. No Salmonella spp. was isolated in the examined samples. In the same collected samples, % 72 Penicillium spp,, % 54 Aspergillus spp., % 34 Fusarium spp. and % 28 Mucor spp. were isolated and identified. At the end of (his study, it was concluded that the microbiological analysis is important as much as chemical, microscopic and sensory analysis of feeds for determining the feed quality and the microbiological quality of feed has to be involved in "feed quality concept" and put into Ihe practice.